1996
DOI: 10.1002/(sici)1097-0258(19960330)15:6<581::aid-sim182>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Misclassification of Smoking Habits as a Source of Bias in the Study of Environmental Tobacco Smoke and Lung Cancer

Abstract: The relationship of environmental tobacco smoke to lung cancer risk in lifelong non-smokers is commonly studied using marriage to a smoker as the index of exposure. As smokers tend to marry smokers, relative risk estimates will be biased if some current or former smokers are misclassified as lifelong non-smokers. This paper shows how various factors affect the magnitude of the bias and describes a method for obtaining misclassification-adjusted relative risk estimates. Application of the method to U.S. and Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…In addition, smoking status (ever vs. never) was used in our study. This could introduce some bias, because the risk of former smokers decreases over time (Lee and Forey 1996). However, the bias is expected to be small in our study because most of the ever-smokers are current smokers in our data set.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, smoking status (ever vs. never) was used in our study. This could introduce some bias, because the risk of former smokers decreases over time (Lee and Forey 1996). However, the bias is expected to be small in our study because most of the ever-smokers are current smokers in our data set.…”
Section: Discussionmentioning
confidence: 92%
“…Thomas et al (75), Gustafson (76), and others provide an overview of issues and techniques (77)(78)(79)(80)(81). These works all deal with environmental as opposed to genetic association.…”
Section: Phenotype Errormentioning
confidence: 99%
“…31,32 Together, these two facts imply that studies of self-reported never smokers may observe that ETS is positively associated with risk of a disease caused by smoking even when no true risk of ETS exposure exists. 33 This misclassification bias has been widely discussed for lung cancer, although opinions differ as to its importance. 32,34-36 As smoking is Table 3.…”
Section: Misclassification Of the Subject's Smoking Statusmentioning
confidence: 99%